Meta‐analysis: antibiotic therapy for small intestinal bacterial overgrowth. Issue 8 (4th September 2013) - Shah, S. C.; Day, L. W.; Somsouk, M.; Sewell, J. L.
Summary: Background: Small intestinal bacterial overgrowth (SIBO) is an under‐recognised diagnosis with important clinical implications when untreated. However, the optimal treatment regimen remains unclear. Aim: To perform a systematic review and meta‐analysis comparing the clinical effectiveness of antibiotic therapies in the treatment of symptomatic patients with documented SIBO. Methods: Four databases were searched to identify clinical trials comparing effectiveness of: (i) different antibiotics, (ii) different doses of the same antibiotic and (iii) antibiotics compared with placebo. Data were independently extracted according to predetermined inclusion and exclusion criteria. Study quality was independently assessed. The primary outcome was normalisation of post‐treatment breath testing. The secondary outcome was post‐treatment clinical response. Results: Of 1356 articles identified, 10 met inclusion criteria. Rifaximin was the most commonly studied antibiotic (eight studies) with overall breath test normalisation rate of 49.5% (95% confidence interval, CI 44.0–55.1) (44.0%–55.1%) then (46.7%–55.5%), then (4.6%–17.8%). Antibiotic efficacy varied by antibiotic regimen and dose. Antibiotics were more effective than placebo, with a combined breath test normalisation rate of 51.1% (95% CI 46.7–55.5) for antibiotics compared with 9.8% (95% CI 4.6–17.8) for placebo. Meta‐analysis of four studies favoured antibiotics over placebo for breath test normalisation with an odds ratio of 2.55 (95% CI 1.29–5.04). Clinical response was heterogeneously evaluated among six studies, but tended to correlate with breath test normalisation. Conclusions: Antibiotics appear to be more effective than placebo for breath test normalisation in patients with symptoms attributable to SIBO, and breath test normalisation may correlate with clinical response. Studies were limited by modest quality, small sample size and heterogeneous design. Additional higher quality clinical trials of SIBO therapy are warranted.